Cercozoan diversity of spring barley grown in the field is strongly plant compartment specific - Sacharow, Julia; Ratering, Stefan; Quiroga, Santiago; Geißler-Plaum, Rita; Schneider, Bellinda; Österreicher Cunha-Dupont, Alessandra; Schnell, Sylvia (Frontiers in Microbiomes, 2024)
Protists are an important part of the plant holobiome and influence plant growth and pathogenic pressure as consumers. Hordeum vulgare is one of the most economically important crops worldwide, and its yield depends on optimal environmental plant-growth conditions and pathogen pressure. This study aimed to analyse the natural compositions of the cercozoan diversity, one of the most important and dominant protist phyla, of spring barley at different developmental stages, from different plant compartments over two years. Hordeum vulgare bulk soil samples were taken before seeding and after harvest on an organic farming field. Bulk soil, rhizosphere soil, roots and leaves were sampled at the flowering and ripening stages, and analysed with cercozoan-specific primers. Results showed a clear dominance of the families Sandonidae, Allapsidae, Cercomonadidae, Glissomonadida and Rhogostomidae in all sample types. Separated analyses of root, leaf and soil samples showed that members of the family Sandonidae were strongly enriched in leaf samples, while members of the Allapsidae family were enriched in the roots. No compositional differences were detected between the different plant developmental stages, except for the beta diversity of the leaf samples at the flowering and ripening stages. It can be concluded that the cercozoan diversity of spring barley is primarily affected by the plant compartment and not by the plant developmental stage. Further studies are needed to analyze the cercozoan community in greater taxonomic depth and to target their ecological function.